Use of graphene and niobium in medical practice: a narrative literature review (Research, Society and Development, 2022)
Introduction: The so-called nanomaterials are considered by many, materials that have their structure restricted to dimensions from 1 to 100 nm. Nanomaterials have a wide range of applications in biomedicine, food and agriculture, drugs and vaccines, and especially in catalysis. Objective: to show the applications of graphene and niobium nanomaterials in medicine, highlighting their promising results in this field. Methodology: This is a descriptive research of the narrative literature review type. The search was carried out through online access in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases Information Services, November 2021. Results and discussion: Reduced graphene oxide has been shown to be an excellent photothermal agent, allowing the efficient elimination of tumors in in vivo experiments, as well as, due to the excellent electrical conductivity of graphene, it promises to improve the conversion of synapses into motion. Furthermore, the use of niobium is growing in the medical field as an alloying element to increase the mechanical strength of biocompatible orthopedic implants. Final considerations: Thus, it is possible to say that there are many benefits that graphene and niobium, interconnected with nanotechnology, will generate to humanity, and especially to medical advances.